2017
DOI: 10.1590/0102-311x00148915
|View full text |Cite
|
Sign up to set email alerts
|

Gastos privados com saúde bucal no Brasil: análise dos dados da Pesquisa de Orçamentos Familiares, 2008-2009

Abstract: Este é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution, que permite uso, distribuição e reprodução em qualquer meio, sem restrições, desde que o trabalho original seja corretamente citado.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 16 publications
0
11
0
10
Order By: Relevance
“…A higher income can facilitate paying for dental services, the purchasing of dental products and adherence to health insurance, while greater schooling can be translated into a higher level of information about the importance of regular visits to the dentist 1,18 . A study found that Brazilians spent an average of R$42.19 reais on dental care services and R$10.27 reais on oral hygiene products 19 . In addition, spending on health and insurance plans increases with age, favoring the access of richer elderly persons to this type of coverage 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher income can facilitate paying for dental services, the purchasing of dental products and adherence to health insurance, while greater schooling can be translated into a higher level of information about the importance of regular visits to the dentist 1,18 . A study found that Brazilians spent an average of R$42.19 reais on dental care services and R$10.27 reais on oral hygiene products 19 . In addition, spending on health and insurance plans increases with age, favoring the access of richer elderly persons to this type of coverage 19 .…”
Section: Discussionmentioning
confidence: 99%
“…A study found that Brazilians spent an average of R$42.19 reais on dental care services and R$10.27 reais on oral hygiene products 19 . In addition, spending on health and insurance plans increases with age, favoring the access of richer elderly persons to this type of coverage 19 . In the USA, elderly persons over the age of 65 are covered by public health insurance (Medicare), which covers individual expenditure on medical costs 6 .…”
Section: Discussionmentioning
confidence: 99%
“…O fato de o gasto absoluto com assistência odontológica ser superior entre os mais ricos sugere uma maior disponibilidade de recursos financeiros ou o pagamento de serviços mais caros, como os procedimentos odontológicos especializados (implantes, próteses e aparelhos ortodônticos), que contabilizam cerca de 85% das despesas referidas com odontologia 9 . Além disso, indivíduos com renda mais elevada optam pelo pagamento direto de serviços odontológicos privados a ter que arcar com algumas desvantagens provenientes da utilização dos serviços do setor público, tais como filas de espera, ou então adquirem planos odontológicos que objetivam financiar ou até mesmo reduzir os custos de seus tratamentos 18 .…”
Section: Discussionunclassified
“…Informações sobre os gastos privados com saúde das famílias brasileiras podem ser obtidas pelas Pesquisas de Orçamentos Familiares (POF), realizadas periodicamente, desde 1987, pelo Instituto Brasileiro de Geografia e Estatística (IBGE) e também do componente de saúde das Pesquisas Nacionais por Amostra de Domicílios (PNAD) de 1998, 2003 e 2008. Diversos trabalhos publicados valendo-se dessas bases de dados têm como foco a análise do perfil do gasto das famílias e a questão distributiva a ele relacionada 6,7,8,9,10 . Tais estudos apontam que a renda e escolaridade são fator determinantes dos gastos privados com saúde, ou seja, quanto maior a renda e maior a escolaridade, maior o gasto absoluto com saúde.…”
unclassified
See 1 more Smart Citation